2014
DOI: 10.1371/journal.pone.0113392
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Human Normal Sperm Morphology Rate on Cycle Outcomes and Assisted Reproductive Methods Selection

Abstract: Sperm morphology is the best predictor of fertilization potential, and the critical predictive information for supporting assisted reproductive methods selection. Given its important predictive value and the declining reality of semen quality in recent years, the threshold of normal sperm morphology rate (NSMR) is being constantly corrected and controversial, from the 4th edition (14%) to the 5th version (4%). We retrospectively analyzed 4756 cases of infertility patients treated with conventional-IVF(c-IVF) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
1
23
1
1
Order By: Relevance
“…Some studies had shown that the ectopic rate was significantly higher in ICSI assisted reproduction than that in c-IVF assisted reproduction due to fewer risk factors in c-IVF assisted reproduction [19]. We also observed that the abortion rate was improved in ICSI assisted reproduction which was not consistent with Li's study [11]. Previous studies had indicated that, for teratozoospermia patients, ICSI assisted reproduction could reduce the abortion rate.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Some studies had shown that the ectopic rate was significantly higher in ICSI assisted reproduction than that in c-IVF assisted reproduction due to fewer risk factors in c-IVF assisted reproduction [19]. We also observed that the abortion rate was improved in ICSI assisted reproduction which was not consistent with Li's study [11]. Previous studies had indicated that, for teratozoospermia patients, ICSI assisted reproduction could reduce the abortion rate.…”
Section: Discussioncontrasting
confidence: 85%
“…Some studies have demonstrated that ICSI assisted reproduction have a higher fertilization rate compared with c-IVF assisted reproduction for the patients with NSMR<4% [11]. And in a large retrospective study for NSMR<4% patients, Li et al [11] observed that the abortion rate was significantly lower in ICSI group than that in IVF group (6.32 versus 13.6%; p<0.001).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(2014) при процедуре ЭКО в группе, где NSMR составлял ≥14 %, частота оплодотворения была значительно вы-ше, чем в группе ИКСИ (р <0,05), в группе с NSMR 4-14 % масса при рождении близнецов была значи-тельно выше, чем в группах ИКСИ, а в группе с NSMR менее 4 % показатель невынашивания беременности значительно превысил аналогичный показатель в груп-пе ИКСИ. Таким образом, авторы пришли к выводу, что показатель NSMR положительно связан с резуль-тативностью методов, и рекомендовали при NSMR свыше 4 %, считать предпочтительным проведение ИКСИ, а при NSMR 4 % и более -ЭКО [52].…”
unclassified